SCARS ON THE BODY OF THE CITY: MURDER OF JEWS IN RIVNE DURING THE HOLOCAUST (City: History, Culture, Society, 2020)
The article is devoted to the coverage of the Holocaust in Rivne. Unfortunately, apart from the shootings in the Sosonky tract in November 1941, other cases of the extermination of Jews are covered very little in the academic literature, and some locations of extermination are not specified. In modern historiography of the Holocaust, all the facts of the murder of Jews in Rivne have not yet been investigated, which is a kind of white spot. In an attempt to locate such places, the article presents the testimonies of victims (Jews), observers (non-Jews), Germans and police officers (executioners).           The first victims of the Nazi occupation in the city were residents who died in the bombing and air raids. In the summer of 1941, the Jews became victims of shootings.  Their initial elimination took place in the context of the struggle against "Jewish Bolshevism" when those who supported the previous government and those who were able to lead the resistance - men and intellectuals - were killed.  Throughout the German occupation, Jews found their deaths in the Rivne prisoners of war camps Shtalag 360, in the local prison, in the Vydumka tract. Among the discovered unknown pages of the history of the Rivne, the ghetto is the murder of non-native Viennese Jews during its liquidation. There is a possibility that Jews from the Rivne district are among the prisoners of the Rivne ghetto.Members of the forensic medical examination of the National Palace of Culture, which investigated the crimes of the occupiers in Rivne and Rivne region, concluded that the destruction of civilians and prisoners of war in Rivne was carried out by mass shootings with «killer machines», killing with carbon monoxide, іn some cases, people were buried alive in graves. Identifying the exact quantitative losses of the Jewish population of Rivne in these locations is a very difficult task. We can cover only 17.5 thousand Holocaust victims in Sosonky, but in other locations where Jews were killed along with Ukrainians, Poles, etc., it is impossible to do so. The information given earlier by researchers about the number of 22,000 to 23,000 Jews were killed during the Holocaust in the city, in our opinion, should be changed in the direction of research.
Keywords: Jews; The Holocaust; Rivne; Camps of the prisoners of war; Sosonky; Rivne Prison; White str.